Alternative 3′ UTRs direct localization of functionally diverse protein isoforms in neuronal compartments. Issue 5 (22nd December 2018) - Ciolli Mattioli, Camilla; Rom, Aviv; Franke, Vedran; Imami, Koshi; Arrey, Gerard; Terne, Mandy; Woehler, Andrew; Akalin, Altuna; Ulitsky, Igor; Chekulaeva, Marina
Abstract: The proper subcellular localization of RNAs and local translational regulation is crucial in highly compartmentalized cells, such as neurons. RNA localization is mediated by specific cis- regulatory elements usually found in mRNA 3′UTRs. Therefore, processes that generate alternative 3′UTRs—alternative splicing and polyadenylation—have the potential to diversify mRNA localization patterns in neurons. Here, we performed mapping of alternative 3′UTRs in neurites and soma isolated from mESC-derived neurons. Our analysis identified 593 genes with differentially localized 3′UTR isoforms. In particular, we have shown that two isoforms of Cdc42 gene with distinct functions in neuronal polarity are differentially localized between neurites and soma of mESC-derived and mouse primary cortical neurons, at both mRNA and protein level. Using reporter assays and 3′UTR swapping experiments, we have identified the role of alternative 3′UTRs and mRNA transport in differential localization of alternative CDC42 protein isoforms. Moreover, we used SILAC to identify isoform-specific Cdc42 3′UTR-bound proteome with potential role in Cdc42 localization and translation. Our analysis points to usage of alternative 3′UTR isoforms as a novel mechanism to provide for differential localization of functionally diverse alternative protein isoforms.